Physico-chemical Properties of Tunisian Bentonitic Clays - Srasra, E.; Trabelsi-Ayedi, M. (Asian Journal of Chemistry, 2010)
Bentonites, which consist essentially of clay minerals belonging to the smectite group, have a wide range of chemical and industrial uses. The structure, chemical composition, exchangeable ion type and small crystal size of smectite are responsible for several properties, including a large chemically active surface area, a high cation exchange capacity and interlamellar surface having unusual hydration characteristics. Two samples collected from Gafsa and Kef deposits, are studied by some physico-chemical methods. Results of X-ray diffraction, chemical analysis, infrared spectroscopy, cation exchange capacities and specific and total surface confirm the general smectitic character of the collected samples .